2009
DOI: 10.1103/physrevd.79.123501
|View full text |Cite
|
Sign up to set email alerts
|

Transient and late time attractor tachyon dark energy: Can we distinguish it from quintessence?

Abstract: The string inspired tachyon field can serve as a candidate of dark energy. Its equation of state parameter w varies from 0 to −1. In case of tachyon field potential V (φ) → 0 slower(faster) than 1/φ 2 at infinity, dark energy(dark matter) is a late time attractor. We investigate the tachyon dark energy models under the assumption that w is close to −1. We find that all the models exhibit unique behavior around the present epoch which is exactly same as that of the thawing quintessence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…They showed that under the slow‐roll conditions, a scalar field with a variety of potentials V (φ) evolves in a similar fashion and one can derive a generic expression for the equation of state for all such scalar fields. Similar results were later obtained for the case of phantom (Scherrer & Sen 2008b) and tachyon scalar fields (Ali et al 2009; Sen et al 2010). It was demonstrated that under slow‐roll conditions, all of them have identical equations of state and hence cannot be distinguished, not at least at the level of background cosmology.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…They showed that under the slow‐roll conditions, a scalar field with a variety of potentials V (φ) evolves in a similar fashion and one can derive a generic expression for the equation of state for all such scalar fields. Similar results were later obtained for the case of phantom (Scherrer & Sen 2008b) and tachyon scalar fields (Ali et al 2009; Sen et al 2010). It was demonstrated that under slow‐roll conditions, all of them have identical equations of state and hence cannot be distinguished, not at least at the level of background cosmology.…”
Section: Introductionsupporting
confidence: 82%
“…With the slow‐roll condition satisfied, i.e. λ i x ≪ 1, it was shown earlier that models with different potentials have an identical w ( a ) for both scalar and tachyon fields (Scherrer & Sen 2008a,b; Ali et al 2009). Although we show equations of state for some models which are more than w =−0.8 at present, these models are practically ruled out by the current observational data.…”
Section: Background Evolution For Thawing Dark Energy Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown that under such conditions thawing models with variety of potentials evolve in a similar fashion and results in a unique analytic expression for the equation of state w ( z ). This result was later extended to the case of phantom models (Scherrer & Sen 2008b) and tachyon scalar field models (Ali, Sami & Sen 2009). In another work, thawing models (for both canonical and non‐canonical scalar fields) have been studied without the assumption of the slow roll condition (Sen, Sen & Sami 2010).…”
Section: Introductionmentioning
confidence: 83%
“…The scalar field models (such as quintessence, phantom, quintom, tachyon, K-essence, dilaton and Chaplygin) are often regarded as an effective description of an underlying theory of DE [10]. The scalar field models can alleviate the fine tuning and coincidence problems [11]. Scalar fields naturally arise in particle physics including supersymmetric field theories and string/M theory.…”
Section: Introductionmentioning
confidence: 99%